PENERAPAN MEDIA FLIPBOOK “KOMIK ZAMAN NOW” PADA PEMBELAJARAN SENI UNTUK MENINGKATKAN KREATIVITAS SISWA KELAS IV SD - Karin Widya Ayuningtyas; Eka Titi Andaryani; Deni Setiawan (STKIP Subang, 2025)
Fine arts learning in elementary schools often faces obstacles in fostering student creativity, especially in storytelling drawing (comic) materials. Conventional methods and the lack of interactive media cause students to have difficulty visualizing ideas and storylines, resulting in monotonous artwork. This study aims to analyze the effectiveness of implementing